Análise dos facilitadores e das barreiras para integração e compartilhamento de informações de segurança pública: um estudo de caso no Centro de Comando e Controle do Rio Grande do Sul - Santos, Ivens Giuliano Campos dos (Universidade do Vale do Rio dos Sinos, 2018)
With the creation of the Integrated Command and Control Center (CICC) and after major events such as the World Cup and the Olympics, and the CICC was perpetuated as a "legacy" for the community of Rio Grande do Sul, the question arose: what are the facilitating factors and the barriers to information sharing and integration among public agencies involved in the Rio Grande do Sul Integrated Public Security Command and Control Center (CICC)? Using the qualitative method, in a case study, the survey involved key informants as managers of institutions involved in CICC and IT managers for data collection. The research analyzed the answers of the interviewees by theoretical categories indicated by the literature. The CICCR (Integrated Command and Control Center), in the case of Rio Grande do Sul called the Command and Control Integrated Command Department, is the coordinating element of the Regional Security Operation, which aims to ensure the flow of information of interest national level for the CICCN (Integrated Command and National Control Center) and operational interest for ancillary structures. Analyzing the interviews and an observed critical event, three theoretical perspectives were considered. In political terms, there was the collaboration of the parties and political will. Regarding the managerial and organizational perspective, it is important to highlight the difficulties in planning and calculating the costs of the operation. In the technological perspective, the adequate planning of the technology to be used during operations and its constant updating is important. There are factors that can be both facilitators and barriers depending on how they are worked. In the same way, although technology plays an important role, the political and managerial perspective overlaps.
Keywords: Setor público; Compartilhamento; Integração de informações de Segurança Pública; Centro de Comando e Controle Integrado; Public sector; Sharing; Integration of public safety information; Center and integrated control and control; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis